Critical care medicine principles of diagnosis and management in the adult - Parrillo, Joseph E.; Dellinger, R. Phillip (Elsevier/Saunders, 2014)
Take the best possible care of adult critical care patients with Critical Care Medicine: Principles of Diagnosis and Management in the Adult! Editors Dr. Joseph Parrillo and Dr. Phillip Dellinger, two of the most respected names in critical care medicine, combine their extensive knowledge with that of hundreds of top authorities in the field to bring you expert, state-of-the-art answers to any clinical question you may face in the intensive care unit. Learn from ICU specialists worldwide with contributions from an increased number of international authorities. Effectively manage common complications in the ICU with updated coverage of severe sepsis, septic shock, surgical infections, neurogenic and anaphylactic shock, severe heart failure, acute coronary syndromes, and Acute Respiratory Distress Syndrome.